Kunai: A static analysis framework for Android apps - Eduardo Blázquez; Juan Tapiador (SoftwareX, 2023)
This paper describes Kunai, a C++ library that offers static analysis functionalities for Android apps. Kunai’s main goal is to provide analysts and researchers with a framework to conduct advanced static analysis of Dalvik code, including parsing, disassembling and code analysis. Written in C++, it focuses on efficiency and an extensible software architecture that enables the integration of new analysis modules easily. Kunai is particularly suitable for the development of analysis pipelines that need to scale up to process large app datasets.